Pengawasan Pendristribusian Penggunaan Gas LPG 3 Kg Terhadap Masyarakat Oleh Dinas Pendistribusian Dan Perdagangan Kota Tanjung Balai - Nikmah Kholilah Lubis; Suhairi Suhairi (Universitas Labuhanbatu, 2022)
This study analyzes the supervision of the distribution of the use of 3 kg LPG gas to the community by the distribution and trade office of the city of Tanjung Balai. This study uses a descriptive qualitative research approach that collects data through interviews and uses primary and secondary data sources. The results of this study are that the supervision carried out by the Department of Industry and Trade of the City of Tanjung Balai in the distribution of 3 Kg LPG gas in Tanjung Balai City is not optimal, this is because there are still agents and distributors of 3 Kg LPG gas who have not fully carried out the distribution process in accordance with regulations that have been set by the government, namely Presidential Decree no. 104/2007 concerning the Supply, Distribution, Pricing of 3 Kg LPG Cylinders and the Decree of the Mayor of Tanjung Balai No. 237 of 2009 concerning the Determination of the Highest Retail Price of 3 Kg LPG Cylinders in the City of Tanjung Balai. such as differences in retail selling prices, cylinder circulation and misuse of 3 Kg LPG gas, lack of public awareness in the safety of 3 Kg LPG gas distribution, as well as irregularities in distributing 3 Kg LPG gas in Tanjung Balai City. The factors that hinder the implementation of supervision of the Department of Industry and Trade of Tanjung Balai City in the distribution of 3 Kg LPG gas are as follows: Limited human resources in conducting supervision, there is no firm sanction from the Tanjung Balai City Government and the Industry and Trade Office. Tanjung Balai City.